Gentile Gods at the Eschaton: A Reconsideration of Paul's Principalities and Powers in 1 Corinthians 15 - Wasserman, Emma (Journal of Biblical literature, 2017)
This article argues that Paul's principalities and powers in 1 Cor 15:23-24 are best understood as a subordinate host of gentile gods. Like texts such as Isa 24, the Book of the Watchers, the Animal Apocalypse of Enoch, and Dan 10, Paul treats gentile gods as belonging to the lower ranks of the divine order and envisions a time when they will be judged, punished, or destroyed. These traditions also shed light on the brief appearance of Christ's enemies in 15:23-24 and the heavy emphasis on Christ's submission in 15:24-28. Paul alludes to conflict in ways that suppress the possibility of rivalry, competition, and coup, in part by imagining a battle that takes place in the lower ranks where it is carried out by a warrior deputy, and in part by strategically telescoping to focus attention on the incomparable standing of the supreme God over all. These findings undermine a number of popular theories about evil forces and powers that are alleged to be central to Paul's apocalyptic thinking here and elsewhere in the letters.